Moving Memories: Maslyn Williams' The Happy Island. Issue 3 (3rd November 2017) - Connelly, Andrew
ABSTRACT: The Happy Island is a documentary film about a hospital on Gemo Island, near Port Moresby in present-day Papua New Guinea. Patients with either leprosy or tuberculosis were isolated there. The documentary was made in 1958 and produced by Maslyn Williams for the Australian Commonwealth Film Unit as part of a series intended to communicate the work of the Australian administration in the territories of Papua and New Guinea. It offers a rich visual record of the Gemo community, which was run by European and Samoan sisters of the London Missionary Society with the assistance of residents and visiting members of the mission and administration. While prompting many questions, including questions about accuracy and purpose, and put to many uses beyond its makers' original intentions, the film is also of great value today as an historical document.